GENERAL PRINCIPLES OF LANGUAGE MATERIAL COMPARISON - Zakirova Dilrabo Khaidarovna (Western European Studies, 2024)
The article discusses the increasing interest of linguists in the problems of comparative language learning. Particular attention is focused on those areas and branches that allow, on the one hand, to supplement or develop the idea of each nation about the specifics of the national path within the framework of the general course of civilization, to determine the value of its culture, the originality of the language, and in this regard, a special role is played by comparative linguistics, the main subject of which is the proof and demonstration of similar and different phenomena in the languages and culture of peoples
Keywords: linguistics; specificity; comparison